Building bridges : case studies in collaborative governance in Canada - Rocan, Claude (University of Ottawa Press, 2022)
"The case studies contained in this book show real life examples of complex problems being addressed through collaboration. The problems confronting modern society are complex and do not lend themselves to simple solutions or linear decision making. They require the involvement of many stakeholders. This is often brought about by networks, which bring together a multitude of players in the search for solutions to public policy issues. This can be challenging, as differing viewpoints and personalities, and often conflicting interests need to be acknowledged and reconciled. Yet without the involvement of all interested parties, solutions that emerge will likely be partial, distorted, and short-lived. The cases span a broad spectrum, including issues of poverty reduction, criminal gang reduction, environmental reparation, economic development for First Nations, building age-friendly communities, and co-management of fisheries."--